2021
DOI: 10.1177/2151459321996626
|View full text |Cite
|
Sign up to set email alerts
|

The Use of High Strength Sutures and Anchors in Olecranon Fractures: A Systematic Review

Abstract: Purpose/Background: Olecranon fractures are common, particularly in the elderly osteoporotic population. Although various techniques of fixation are available, the gold standard—tension band wiring (TBW)—has high complication and reoperation rates. We sought to identify current evidence for the use of high-strength suture tension banding methods to determine whether they reduce complications and reoperation rates while maintaining fixation. Methods: A systematic review of several databases was performed accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
0
6
0
2
Order By: Relevance
“…18 Although olecranon nails are commercially available, they are not widely used due to the lack of any strong clinical evidence. There has been some interest in the use of sutures with or without anchors for fixation of olecranon fractures with a recent systematic review 19 suggesting that FibreWire/SutureTape fixation and suture anchor fixation had similar union rates and significantly lower re-operation rates when compared to traditional TBW.…”
Section: 3223mentioning
confidence: 99%
“…18 Although olecranon nails are commercially available, they are not widely used due to the lack of any strong clinical evidence. There has been some interest in the use of sutures with or without anchors for fixation of olecranon fractures with a recent systematic review 19 suggesting that FibreWire/SutureTape fixation and suture anchor fixation had similar union rates and significantly lower re-operation rates when compared to traditional TBW.…”
Section: 3223mentioning
confidence: 99%
“…Nazifi y cols. 7 llevaron a cabo una revisión sistemática de estudios con nivel de evidencia I-V, sobre el uso de suturas fuertes y arpones para las fracturas de olécranon. Solo encontraron nueve artículos publicados, y concluyeron en que el uso de suturas es una alternativa costo-efectiva frente al alambre, ya que disminuye ampliamente la tasa de reoperación.…”
Section: Discussionunclassified
“…4 Se han descrito múltiples opciones quirúrgicas para el tratamiento de las fracturas de olécranon (clavijas con alambre, placas anatómicas, tornillos endomedulares canulados solos o con alambre, clavos endomedulares, banda de tensión con suturas solamente). [5][6][7] Todos estos métodos de fijación tienen como resultado la reducción anatómica, restaurar la movilidad y la consolidación de la fractura.…”
unclassified
“… 20 The suture anchors have a high prevalence of malunion and nonunion complication due to its limited holding strength of the fracture. 21 Further, a biomechanical comparison study of screw osteosynthesis and anatomical plating found that the plate osteosynthesis had better stability for large coronoid shear fractures. 22 However, in cases of coronoid fractures with comminution, the plate or suture could not provide enough stability individually.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study showed that the lasso technique was more stable than the suture anchors or screws fixation alone 20 . The suture anchors have a high prevalence of malunion and nonunion complication due to its limited holding strength of the fracture 21 . Further, a biomechanical comparison study of screw osteosynthesis and anatomical plating found that the plate osteosynthesis had better stability for large coronoid shear fractures 22 .…”
Section: Introductionmentioning
confidence: 99%